Contemporary issues in development : essays in honour of Q.K. Ahmad - Ahmad, Qazi Kholiquzzaman, 1943-; Biswas, Asit K.; Bangladesh Unnayan Parishad; Third World Centre for Water Management (Dhaka : Bangladesh Unnayan Parishad ; Estado de México : Third World Centre for Water Management ; Dhaka : Academic Press and Publishers, 2002)
Contributed articles on diverse issues relating to social and economic development of Bangladesh.
Includes statistical tables.
Includes bibliographical references.
Momiul
Keywords: Economic conditions -- Bangladesh; Bangladesh -- Social conditions; Bangladesh -- Economic conditions; Bangladesh -- Social conditions -- Statistics; Bangladesh -- Economic conditions -- Statistics